Immune control of the basal ganglia network: Interleukin-17 as a key modulator of striatal synaptic plasticity - Andrea Mancini; Laura Bellingacci; Jacopo Canonichesi; Miriam Sciaccaluga; Alfredo Megaro; Elisa Zianni; Maria De Carluccio; Marilena Pariano; Edoardo Emiliano; Alessandro Tozzi; Cinzia Costa; Teresa Zelante; et al. (Neurobiology of Disease, 2025)
The basal ganglia (BG) network exerts a key role in the integration of cortical inputs and is fundamental to motor learning, behavior, emotional responses, and cognitive functions. Little is known about how immune cells and soluble immune mediators influence BG activity. Interleukin-17A (IL-17A) is in the spotlight for its emerging role as a neuromodulator of cortical synaptic transmission and plasticity in physiological and pathological conditions. However, its role at the level of subcortical structures such as the BG circuit is still unclear. In this study, we demonstrate that striatal medium spiny neurons (MSNs) highly express IL-17RA and that the IL-17 axis contributes to the physiological expression of synaptic plasticity in these cells. Indeed, long-term potentiation (LTP) induction was significantly reduced in mice lacking IL-17A or IL-17RA. This effect might rely on an altered glutamatergic transmission, as synaptic expression of NMDAR subunit GluN2B is reduced in mice lacking IL-17A. At the same time, exposure to high concentrations of IL-17A was found to impair LTP induction through modulation of NMDAR currents. These results suggest a dual effect of this cytokine on striatal synaptic plasticity, showing the IL-17 axis as a key neuromodulator of the BG circuit, with potential implications in the pathogenesis of neuroinflammatory and neuropsychiatric disorders.